Governing AI‐Driven Health Research: Are IRBs Up to the Task?. Issue 2 (8th March 2021) - Friesen, Phoebe; Douglas‐Jones, Rachel; Marks, Mason; Pierce, Robin; Fletcher, Katherine; Mishra, Abhishek; Lorimer, Jessica; Véliz, Carissa; Hallowell, Nina; Graham, Mackenzie; Chan, Mei Sum; Davies, Huw; et al.
ABSTRACT: Many are calling for concrete mechanisms of oversight for health research involving artificial intelligence (AI). In response, institutional review boards (IRBs) are being turned to as a familiar model of governance. Here, we examine the IRB model as a form of ethics oversight for health research that uses AI. We consider the model's origins, analyze the challenges IRBs are facing in the contexts of both industry and academia, and offer concrete recommendations for how these committees might be adapted in order to provide an effective mechanism of oversight for health‐related AI research.